Prevalence of falciparum malaria parasitaemia and risk factors associated among residents of a peri urban community in Akure, Nigeria - Oluwaseun Bunmi Awosolu, Zary Shariman Yahaya, Kehinde Oluwatobi Elegbede (International Journal of Advanced Science and Technology, 2020)
Malaria is a serious global public health challenge caused by parasite belonging the genus Plasmodium and it is known to have hindered growth and development in Nigeria and worldwide. An investigation on the prevalence and risk factors enhancing local transmission of Plasmodium falciparum was carried out in Ipinsa, Akure South Local Government Area (LGA) of Ondo State, Nigeria. Volunteered individuals which totaled three hundred (300) were examined for the parasite using thick and thin blood smears viewed under the x100 objective lens of the light microscope. The demographic and socio-economic characteristics of the study population were determined through administration of questionnaires to the participants. Overall prevalence of 78.3% was recorded among the participants. Males had a higher rate of infection (80.3%) than females (76.7%) though no significant difference was found (P<0.05). Individuals within the age group of 21 and above had the highest infection prevalence of 95.7% which was significant (P<0.05) compared to individuals within the age group 11 to 16 who had the least rate of infection (57.5%). With respect to sex, the highest parasite density was observed in females (2068 parasites/µl) while the least was observed in males (1806 parasites/µl). The results also showed that with respect to age, the highest parasite density was spotted among 5 years and below (2206 parasites/µl) while the least parasite density was observed among 21 years and above (1680 parasites/µl). The subject’s income per month also played a significant (P<0.05) role as a determining factor for malaria infection. The highest malaria infection prevalence of 85.2% was recorded among individuals who earn ≤18000 Naira income/month while the least malaria infection (56.9%) was recorded among those who earn ≥31000 Naira income/month. In view of the outcome of current study, it is apparent that malaria is endemic in Ipinsa and control interventions should be deployed.